Chapter Glossaire terminologique collaboratif et Data-Driven Learning dans le cadre de la traduction du lexique artistique - Dechamps, Christina (Lessico multilingue dei Beni Culturali, 2023)
This chapter focuses on the role of corpora, in particular the LBC corpus (Lessico dei Beni Culturali), in the training of (future) translators. First, a variety of teaching methodologies, such as «task», «Learners' Bilingual Lexicography/Terminography», «Corpus-Based/ Data-Driven Learning», and «strategic competence» will be re-examined, taking into account the use of corpora at all stages of translators' training. The article will then illustrate a case study involving two translation classes focusing on architecture and art history (including Gothic and Renaissance art). These have led to the writing of a bilingual glossary (Portuguese-French and French-Portuguese), a collaborative and ongoing project for students in translation.